Appointment of Key Officials under Semi-Presidentialism: Case of Lithuania - Jastramskis, Mažvydas (Politologija, 2024)
Both academics who study presidential powers and political practitioners acknowledge that Lithuanian president enjoys the power to appoint high-ranking officials. This article investigates the determinants of success (or failure) of presidential decrees by which nominations of high-ranking public officials are submitted to Seimas. Presented theory and results are also discussed in a wider context of literature on semi-presidentialism: what does this power say about the role of presidents and the functioning of such regimes? Analysis employs an original data set, which consists of 337 decrees by presidents of Lithuania from 1993 to 2023 that were submitted to Seimas for consent regarding the appointment of respective public officials. The statistical analysis is complemented by information from semi-structured interviews with several high-ranking politicians. The study reveals several key points. First, high success rate of decrees (about 92.7 percent) is explained by the incentives of the constitutional algorithm and the informal practice of coordinating nominations between the president and the ruling majority before submitting them to Seimas. Second, quantitative analysis and qualitative interviews reveal that the success of decrees increases with the judicial appointments that are advised by a body of experts (Council of Judges) and decreases with appointments to heads of institutions. Third, some cases can also be explained by personal characteristics of nominees: age (result of quantitative analysis) or their self-presentation to Seimas (semi-structured interviews). Fourth, cohabitation – when the president and the parliamentary majority are of different political camps – only partially explains the success of decrees. Some unsuccessful decrees occur because of a short-term drop in the “temperature” of intra-executive relationship. However, this drop usually bounces back to cooperation phase – thus, the power to appoint high-ranking officials contradicts popular paradigm of literature on semi-presidentialism, namely that sees the relationship between president and government as competitive. The president himself together with the system of checks and balances around this power almost ideally embody the moderating power: important condition is that the moderator himself is also constitutionally “moderated”.
Keywords: semi-presidentialism; appointment power; key officials; cohabitation